Host specific reproductive benefits, host selection behavior and host use pattern of the pinnotherid crab Calyptraeotheres garthi - Ocampo, Emiliano Hernan (2012)
In organisms using a wide variety of refuges, both the cost and benefits to the users might be refuge-specific. Under these circumstances, users using mechanisms (e.g., behavioral preference) that allow them to find and colonize refuges in which net benefits are maximized are expected to be selected by the environment. Herein, we tested the hypothesis that resource generalists display strong preferences for resources that provide the greatest reproductive benefits using Calyptraeotheres garthi, a crab that inhabits the limpets Crepidula cachimilla and Bostrycapulus odites in the south-western Atlantic. In the field, female crabs inhabiting C. cachimilla featured larger average body size, and subsequently, larger average fecundity and brood weight than those inhabiting B. odites. Thus, C. cachimilla is a higher quality host for C. garthi compared to B. odites. In contrast to expectations, host selection experiments revealed that female crabs were attracted to the host species from which they were collected and not to the host species that provided the greatest reproductive benefits (C. cachimilla). Host chemical and/or visual cues imprinted in crabs early during ontogeny (soon after colonization of their first host), rather than genetic differences, may explain the source-host fidelity of C. garthi. In the two hosts, females of C. garthi lead a solitary lifestyle and appear to inhabit the same host individual for long periods of time as indicated by the close relationship between female crab and host body size. The frequency of male–female pairs within host individuals was lower than expected by chance alone. Also, males were, on average, smaller than females and did not appear to inhabit the same host individual for long periods of time. The above suggests that males might be using a pure‐search mating strategy, continuously roaming among host individuals in search of receptive females. The details of the mating system of C. garthi need to be further investigated.